2011
DOI: 10.1590/s1516-89132011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agitation speeds and aeration rates on the Xylanase activity of Aspergillus niger SS7

Abstract: In this study, the effect of agitation and aeration rates on xylanase activity of Aspergillus niger SS7 in 3-litre stirred tank bioreactor was investigated. The agitation rates tested were 100, 200 and 300 rpm at each airflow rates of 0.5, 1.0 and 1.5 vvm. The maximum xylanase activity in mono-agitator system was at the agitation speed of 200 rpm and aeration rate of 1.0 vvm. In bi-agitator system, at low agitation speed (100 rpm), the xylanase activity was enhanced by 13% compared to mono-agitator system for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…unclear, similar results were obtained with other fungi with xylanase activity 14 . In addition, increasing the airflow rate induced the formation of foam, causing a large number of cells to adhere firmly to the wall of the fermentor, thus preventing them from obtaining sufficient nutrients from the culture medium.…”
Section: Figsupporting
confidence: 87%
“…unclear, similar results were obtained with other fungi with xylanase activity 14 . In addition, increasing the airflow rate induced the formation of foam, causing a large number of cells to adhere firmly to the wall of the fermentor, thus preventing them from obtaining sufficient nutrients from the culture medium.…”
Section: Figsupporting
confidence: 87%
“…However, although k L a values increased with agitation and aeration rates, they verified that too high k L a had a negative effect on glycoprotein production due to the high shear force caused by high agitation rate, which could destroy the structure of cell and mycelium, and affect the biosynthesis of glycoprotein. The harmful effect of the shear forces due to the higher agitation rate has been reported to cause a reduced enzyme production in some filamentous fungi by other authors [19,20,43,47].…”
Section: Relation Of the Volumetric Oxygen Transfermentioning
confidence: 94%
“…The lower enzyme production observed at 250 rpm when compared to 150 rpm can be related to the shearing effect of the STB turbines. In practice, it has been often reported that the shear stress imposed on mycelial microorganisms at vigorous agitations could lead to morphological and physiological changes, leading to a decrease in enzyme productivity [19,20,43]. In addition, the highest enzymatic activity (cellulase, xylanase, and 150 rpm and 4 vvm (white circle); 250 rpm and 2 vvm (black square); and 250 rpm and 4 vvm (white square).…”
Section: Influence Of Aeration and Agitation Rates In The Enzymatic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters are best controlled in processes which involve submerged cultivation (Submerged Bioprocess -SmgB) due to the great homogeneity of the culture medium (Colla et al, 2010;Colla et al, 2016). Aeration of growing microbial culture can be ensured by inserting air into the culture medium and by agitation, resulting in an increased interface between gas and liquid capable of reducing the size of the air bubbles, making oxygen more easily accessible to the cells (Bakri et al, 2011). However, the intensity of agitation should remain within a narrow range to keep the damage effect in the system at a minimum level (Kozma et al, 2006).…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%